Eratosaster jenae - Mah, Christopher L. (Zenodo, 2011)
Eratosaster jenae nov. sp. (Figure 10 A–D) Diagnosis. Body strongly stellate. Abactinal plates strongly convex. Abactinal, marginal, and actinal plates bare and smooth with only peripheral granulation. Abactinal, marginal, and actinal plates with large conical spines. Furrow spines elongate, forming distinct spiny fringe on tube foot furrow. Subambulacral spine also elongate similar in size to furrow spines. Etymology. The genus is derived from the Greek Eratos for “lovely” and – aster for “star”. The species epithet, “ jenae ” is named for Dr. Jen Hammock, administrator of the US Antarctic Research Program, which has supported Antarctic biodiversity research and collections. Distribution. South Atlantic (Scotia Sea), Burdwood Bank. 339–1886 m. Material examined. HOLOTYPE: USNM 1149358 Burdwood Bank 54°42’S, 56° 36’ W, 339– 357 m. Coll. R/V Eltanin st. 1593, 14 March 1966 (1 dry spec. R=4.2, r=1.3). PARATYPES: USNM 1149359, Scotia Sea, SE of Burdwood Bank, off Falkland Islands 54°0’0”S, 55°53”W, 1879–1886 m. Coll. R/V Eltanin st. 377, 21 December 1962 (1 dry spec., R=4.0, r=1.4). USNM 1149360. Burdwood Bank 54°42’S, 56° 36’ W, 339– 357 m. Coll. R/V Eltanin st. 1593, 14 March 1966. (1 dry spec. R=3.8, r=1.3). Description. Body stellate. Arms elongate, triangular. Interbrachial arcs weakly rounded (Fig. 10 A–B). Disk from (USNM 114358, 114360) is more convex with armtips curled upwards on Burdwood Bank specimens compared to the Scotia Sea specimen (USNM 1149359), which is more flattened. Abactinal plate surface convex, smooth, devoid of accessories (e.g., granules, etc.). Convexity strongest on disk with plates becoming more flattened distally along arm. Abactinal plate in dorsal outline, perfectly circular to oval, often irregular in shape with rounded edges. Fasciolar grooves weakly present. Largest and roundest proximally becoming smaller and more irregular distally towards contact with superomarginal plate series. Abactinal plates present along arm, sometimes to terminal plate but sometimes present only ...